The book thief - Zusak, Markus (New York : Knopf : Distributed by Random House, 2006)
Trying to make sense of the horrors of World War II, Death relates the story of Liesel--a young German girl whose book-stealing and story-telling talents help sustain her family and the Jewish man they are hiding, as well as their neighbors.
Originally published: Australia : Pan Macmillan Australia, 2005.
School Library Journal starred
Wilson's Junior High School
Wilson's Senior High School
Young Adult.
Young Adult
Keywords: Books and reading -- Juvenile fiction; Death -- Juvenile fiction; Jews -- Germany -- History -- 1933-1945 -- Juvenile fiction; Storytelling -- Juvenile fiction; World War, 1939-1945 -- Jews -- Rescue -- Juvenile fiction; Books and reading -- Fiction; Death -- Fiction; Historical fiction; Jews -- Germany -- History -- Fiction; Storytelling -- Fiction; World War, 1939-1945 -- Jews -- Rescue -- Fiction; Books and reading -- Fiction; Death -- Fiction; Historical fiction; Jews -- Germany -- History -- Fiction; Storytelling -- Fiction; World War, 1939-1945 -- Jews -- Rescue -- Fiction; Germany -- History -- 1933-1945 -- Juvenile fiction; Germany -- History -- Fiction; Germany -- History -- Fiction